2020
DOI: 10.2147/cmar.s280096
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Investigation of the Efficacy and Safety of Anlotinib with Immunotherapy in Advanced Non-Small Cell Lung Cancer as Third-Line Therapy: A Retrospective Study</p>

Abstract: This study was designed to assess the clinical efficacy and safety of anlotinib with immunotherapy in advanced non-small cell lung cancer as third-line therapy. Patients and Methods: A total of 101 patients with advanced non-small cell lung cancer who were treated with anlotinib combined with immunotherapy were evaluated for progression-free survival, objective response rate, and disease control rate. Univariate and multivariate analyses were performed to determine the prognostic factors. The main adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…The incidence of adverse events recorded in both groups was low and similar to those reported in the literature [25,[40][41][42][43][44][45][46]. In this study, the proportion of patients rechecking ECG, thyroid function and urine routine was small.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of adverse events recorded in both groups was low and similar to those reported in the literature [25,[40][41][42][43][44][45][46]. In this study, the proportion of patients rechecking ECG, thyroid function and urine routine was small.…”
Section: Discussionsupporting
confidence: 86%
“…A retrospective study showed that ECOG PS score, smoking history and age were predictors of treatment efficacy of anlotinib. 16 This retrospective study also identified a poor PS as independent negative predictors of OS, smoking history and age did not significantly influence mOS. IMpower150 trail have shown that immunotherapy combined with chemotherapy and antivascular therapy is more effective than chemotherapy combined with bevacizumab in patients with advanced non-squamous cell NSCLC.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies have shown that ECOG PS is an important factor for predicting the prognosis of patients with NSCLC. 16 There were more patients with PS score > 1 included in our study. The second is the clinical stage of patients.…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, when combined with PD-1/PD-L1 blockade, anlotinib provided significantly synergistic therapeutic benefits ( 15 ). A retrospective study further demonstrated the efficacy and safety of anlotinib with immunotherapy in advanced NSCLS as a third-line therapy ( 34 ). Based on these studies, we attempted to treat this patient by anlotinib combined with sintilimab, and favorable results were obtained.…”
Section: Discussionmentioning
confidence: 99%